2016
DOI: 10.1152/ajplung.00155.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free hemoglobin: a novel mediator of acute lung injury

Abstract: Patients with the acute respiratory distress syndrome (ARDS) have elevated levels of cell-free hemoglobin (CFH) in the air space, but the contribution of CFH to the pathogenesis of acute lung injury is unknown. In the present study, we demonstrate that levels of CFH in the air space correlate with measures of alveolar-capillary barrier dysfunction in humans with ARDS (r = 0.89, P < 0.001) and in mice with ventilator-induced acute lung injury (r = 0.89, P < 0.001). To investigate the specific contribution of CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 68 publications
1
86
0
1
Order By: Relevance
“…For example, in sepsis, elevated levels of circulating CFH are associated with increased mortality and organ dysfunction (29). In the airspace, elevated levels of CFH are associated with lung epithelial injury and disruption of the alveolar-capillary barrier (30,31). Whether CFH contributes to the pathogenesis of PGD is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in sepsis, elevated levels of circulating CFH are associated with increased mortality and organ dysfunction (29). In the airspace, elevated levels of CFH are associated with lung epithelial injury and disruption of the alveolar-capillary barrier (30,31). Whether CFH contributes to the pathogenesis of PGD is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that more moderate, not easily visualized hemolysis contributes to severe morbidity in sickle cell anemia and paroxysmal nocturnal hemoglobinuria, as well as being a prognostic marker for mortality in critically ill patients. 7,8 Such patients, independent of the etiology of increased free hemoglobin, frequently experience infection, thrombosis, vasculopathy, and organ failure, 7,9 probably in part due to hemolysis. 10 The pathophysiology of how increased free hemoglobin occurs is different in patients who have sickle cell disease/paroxysmal nocturnal hemoglobinuria compared with those who have ABOimmune hemolysis.…”
Section: The Precautionary Principle and Use Of Group A Plasma In Recmentioning
confidence: 99%
“…In a recent publication, Shaver et al found that cell-free hemoglobin levels in the air space correlated with alveolar-capillary barrier dysfunction in humans with acute respiratory distress syndrome (ARDS) (20). Further, they demonstrated that the intratracheal administration of cell-free hemoglobin to mice resulted in alveolar-capillary barrier disruption and acute lung injury (20).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, Shaver et al found that cell-free hemoglobin levels in the air space correlated with alveolar-capillary barrier dysfunction in humans with acute respiratory distress syndrome (ARDS) (20). Further, they demonstrated that the intratracheal administration of cell-free hemoglobin to mice resulted in alveolar-capillary barrier disruption and acute lung injury (20). Interestingly, they also found that the effects of cell-free hemoglobin were mediated by the iron-containing heme moiety of cell-free hemoglobin, as intratracheal administration of free heme was sufficient to increase alveolar permeability in mice (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation